2013
DOI: 10.3201/eid1911.130865
|View full text |Cite
|
Sign up to set email alerts
|

Use of National Pneumonia Surveillance to Describe Influenza A(H7N9) Virus Epidemiology, China, 2004–2013

Abstract: In mainland China, most avian influenza A(H7N9) cases in the spring of 2013 were reported through the pneumonia of unknown etiology (PUE) surveillance system. To understand the role of possible underreporting and surveillance bias in assessing the epidemiology of subtype H7N9 cases and the effect of live-poultry market closures, we examined all PUE cases reported from 2004 through May 3, 2013. Historically, the PUE system was underused, reporting was inconsistent, and PUE reporting was biased toward A(H7N9)-af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(93 citation statements)
references
References 7 publications
2
91
0
Order By: Relevance
“…However, our results suggest hypotheses that should be tested more specifically in future studies. The significant association between LBM density and H7N9 cases in our model provides further support for the hypothesis that LBMs are an important source of H7N9 transmission to humans 3, 10, 28 . A previous study found a tight coupling between climatic variables and seasonal influenza in humans in Hong Kong 29 .…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, our results suggest hypotheses that should be tested more specifically in future studies. The significant association between LBM density and H7N9 cases in our model provides further support for the hypothesis that LBMs are an important source of H7N9 transmission to humans 3, 10, 28 . A previous study found a tight coupling between climatic variables and seasonal influenza in humans in Hong Kong 29 .…”
Section: Discussionsupporting
confidence: 82%
“…Closing LBMs appears to be an effective approach for eradicating or reducing H7N9 infections in humans 10 . In poultry, policies to control H7N9 include culling on positive farms and vaccination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all cases were hospitalized, and 158 (36%) died. The majority of cases [309 [19][20][21][22][23][24][25], and a more equal sex distribution (56% male cases) (27). The reasons for the predominance of older male cases are not understood but have been attributed to cultural practices in which older men may be more likely to shop at LPMs.…”
Section: Epidemiology Of H7n9mentioning
confidence: 93%
“…Surveillance systems for outpatient influenza-like illness and pneumonia of unknown etiology, established following the emergence of SARS and H5N1, were enhanced to greatly increase the numbers of specimens tested throughout China (23,24). Clinician and public awareness for symptoms and testing was raised through traditional and social media such as Weibo, the Chinese equivalent to Twitter (25).…”
Section: Epidemiology Of H7n9mentioning
confidence: 99%